2012
DOI: 10.7314/apjcp.2012.13.9.4587
|View full text |Cite
|
Sign up to set email alerts
|

Poor Treatment Outcome of Neuroblastoma and Other Peripheral Nerve Cell Tumors May be Related to Under Usage of Radiotherapy and Socio-Economic Disparity: A US SEER Data Analysis

Abstract: surgery. Using RT for, especially, adult PNCT patients is a potential way to improve outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…SEER Clinical Outcome Prediction Expert (SCOPE) (Cheung, 2012) was used to mine SEER data and construct accurate and efficient prediction models (Cheung et al, 2001a, b). The data were obtained from SEER 18 database.…”
Section: Methodsmentioning
confidence: 99%
“…SEER Clinical Outcome Prediction Expert (SCOPE) (Cheung, 2012) was used to mine SEER data and construct accurate and efficient prediction models (Cheung et al, 2001a, b). The data were obtained from SEER 18 database.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, an important 10-15 years long-term study demonstrated that moving patients from low income neighborhoods to higher ones improved their obesity and diabetes (Ludwig et al, 2011;2012). In this study examined three SEFs: i) whether the patients lived in a rural as opposed to urban counties; ii) whether the patients lived in a county with a family income equal or lower than $50000 per year as opposed to a higher one; and iii) whether the patients lived in a low college education attainment county were examined.…”
Section: Discussionmentioning
confidence: 99%
“…SEER Clinical Outcome Prediction Expert (SCOPE) (Cheung, 2012) was used to mine SEER data and construct accurate and efficient prediction models (Cheung, 2012). The data were obtained from SEER 18 database.…”
Section: Low Income and Rural County Of Residence Increase Mortality mentioning
confidence: 99%
See 1 more Smart Citation
“…SEER registry has massive amount 7134 of data available for analysis, however, manipulating this data pipeline could be challenging. SEER Clinical Outcome Prediction Expert (SCOPE) is designed and implemented to mine SEER data and construct accurate and efficient prediction models (Cheung, 2012).…”
Section: Methodsmentioning
confidence: 99%